2014
DOI: 10.1155/2014/916212
|View full text |Cite
|
Sign up to set email alerts
|

Power of Proteomics in Linking Oxidative Stress and Female Infertility

Abstract: Endometriosis, PCOS, and unexplained infertility are currently the most common diseases rendering large numbers of women infertile worldwide. Oxidative stress, due to its deleterious effects on proteins and nucleic acids, is postulated to be the one of the important mechanistic pathways in differential expression of proteins and in these diseases. The emerging field of proteomics has allowed identification of proteins involved in cell cycle, as antioxidants, extracellular matrix (ECM), cytoskeleton, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 120 publications
(188 reference statements)
0
71
1
2
Order By: Relevance
“…It is believed that ROS over-production in the reproductive tract may significantly contribute to woman infertility mainly because of the ability of these molecules to exert a toxic effect decreasing oocyte quality [2,38,39]. The follicular fluid may be seen as a "biological window" which reflects all metabolic processes and hormonal microenvironment in which the oocyte matured [40].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that ROS over-production in the reproductive tract may significantly contribute to woman infertility mainly because of the ability of these molecules to exert a toxic effect decreasing oocyte quality [2,38,39]. The follicular fluid may be seen as a "biological window" which reflects all metabolic processes and hormonal microenvironment in which the oocyte matured [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have established that OS have critical roles in the pathophysiology of female infertility . This concept is further enhanced by investigations that have shown OS induced apoptosis in granulosa cells resulting in the reduction of estradiol levels and atresia of follicles . Chaube et al ., showed that OS disrupts granulosa cells‐oocyte communication resulting in decreased quality of oocytes .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, any significant change in MDA levels was not observed after taking selenium supplements in rats [16]. Previous studies have shown that oxidative stress in female reproduction is associated with polycystic ovarian syndrome and endometriosis [57]. Needless to say, these pathologies negatively influence pregnancy rates and IVF outcomes.…”
mentioning
confidence: 99%